Recommendations for future research exploring e-cigarette use and later cigarette smoking in young people: results from a consultation exercise - Conde, M; Pesko, MF; Shahab, L; Begh, R; Lindson, N; Jackson, SE; Kale, D; Kneale, D; Livingstone-Banks, J; Hartmann-Boyce, J (Wiley, 2025)
Background and Aims Exploring the relationship between vaping and smoking in young people is a key area of research that can inform e-cigarette policy. Rigorous evidence mapping and synthesis have highlighted gaps and methodological concerns in the evidence base. This study provides recommendations for the conduct and reporting of future quantitative primary research exploring e-cigarette use and later cigarette smoking in young people (≤29 years).